PROBLEMS FACED BY THE ENGLISH DEPARTMENT STUDENTS IN STUDYING GRAMMAR AT BUNG HATTA UNIVERSITY - Merry Prima Dewi (Universitas Mahaputra Muhammad Yamin, 2019)
This research aimed at finding out the problems faced by the English Department students of Bung Hatta University in studying grammar. Some of the problems in grammar are; the students repeated grammar subject for several times, most of the students did the remedial teaching because they did not fulfill the requirement of the score given by the university. This research is a descriptive quantitative study with the all the English department students as the population. The researcher took stratified proportional sampling in determining the sample. The students were given the questionnaire to find out what are their problems in studying grammar. And to find out more information about students problems, the researcher also did an interview with the grammar lecturer. In understanding grammar materials, students had problems in terms of copying some parts of compulsory grammar book, owning additional grammar book to support their compulsory grammar book, problem in mastering too much material, many time allocated was very limited. In relation to the problems in understanding teachers’ presentation, teacher explains the materials too fast, problem in understanding the language used by the teacher, the media used by teacher. And problem in asking questions when they do not understand teachers’ explanation. Related to the problems of reviewing grammar lesson, the students had problems in terms of reviewing lesson at home. They also had problem in applying grammar rules to communicate outside the class. And students became frustrated when they are failed in grammar subject.